2013
DOI: 10.1055/s-0033-1333747
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Kinesio Taping for Athletes with Medial Elbow Epicondylar Tendinopathy

Abstract: Kinesio taping has also been used for athletes with Medial Elbow Epicondylar Tendinopathy (MET) as an additional treatment method. The purpose of this study was to determine the clinical effectiveness of Kinesio tape on maximal grip strength and absolute and related force sense in athletes with MET when applied to the medial forearm. 27 male athletes who voluntarily participated in this study were divided into a healthy group (n=17) and a MET group (n=10). All subjects were assessed for the maximal grip streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…Few studies have evaluated the effects of KT on proprioception, with diverse findings (13)(14)(15)(16)(17). The hypothesis of the present study, that KT would compensate for JPS deficits caused by muscle fatigue, was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have evaluated the effects of KT on proprioception, with diverse findings (13)(14)(15)(16)(17). The hypothesis of the present study, that KT would compensate for JPS deficits caused by muscle fatigue, was not confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to conventional taping, proprioception improvement due to cutaneous mechanoreceptors stimulation is one of the effects attributed to KT (10). Few studies have evaluated the effects of KT on proprioception (13)(14)(15)(16)(17) and an improvement in grip force sense accuracy (13) and shoulder JPS (16) have been found after the application of KT in healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk of published literature does not favour the use of KT to improve range of motion,6 strength,7 8 proprioception9 and functional performance 10. However, there have been limited positive findings in terms of range of motion11 12 and strength 13.…”
Section: Introductionmentioning
confidence: 99%
“…12 Rousanoglou et al 12 reported a significant relation between jumping height and strength of the knee-extensor muscles in young female volleyball players (P £ .05 and power of analysis >.80). However, findings are conflicting regarding the effects of KT on muscle strength 11,[13][14][15] and jumping, 11,16,17 with reported improvements in healthy participants 8,10,11,14 but not in athletes. 13,14 For instance, jump performance of healthy participants with no history of previous lowerextremity injuries was improved by using KT, 11 but this was not the case in male athletes.…”
mentioning
confidence: 99%